A Brief Online Video-Based Intervention to Promote Mental Health Help-Seeking in the Context of Injuries for Athletes: A pilot study. (November 2022) - Jones, Chantelle; Gulliver, Dr Amelia; Keegan, Dr Richard
Abstract: In the athletic population, sports injuries are often associated with mental health decline. Despite the availability of services, athletes frequently do not seek help for mental health problems. A range of barriers to help-seeking in athletes have been proposed, including poor mental health literacy and limited help-seeking knowledge. To address this, the current study piloted a newly designed online intervention that aimed to increase help-seeking attitudes, intentions, and mental health literacy (specifically depression literacy) in an athletic population. Using a pre-test post-test design, a total of 207 athletes were recruited using online convenience sampling from across Australia. Athletes were from a range of sports and competition levels and were provided a brief online intervention comprising three short educational videos with content addressing: (1) the athlete's response to injury; (2) help-seeking and social support; and (3) signs/symptoms of depression. Participants completed pre- and post-intervention surveys which measured attitudes and intentions towards mental health help-seeking, and depression literacy. Data were analysed using RM-MANOVA, which demonstrated significant within-group improvement from pre-to post-intervention for help-seeking intentions, particularly when seeking help from mental health professionals, F (1, 93) = 24.64, p  < .001, and online/phone services, F (1, 93) = 29.75, p  < .001. Two separate paired samples t -test demonstrated a significant increase from pre-to post-intervention for both help-seeking attitudes, t (206) = 9.04, p  < .001, d = 0.628, and depression literacy, t (203) = 8.66, p  < .001, d = 0.606. The current study shows promise for brief video-based interventions that provide information targeting help-seeking during times of injury. However, further research using a rigorous randomised controlled trial design is needed. Additionally, more work is required to explore if an improvement in attitudes or intentions corresponds with increased help-seeking behaviour. Highlights: Explores help-seeking and mental health literacy regarding injuries in an athletic population. Using a pre-post-test study design, with 3 short online educational videos. Intervention focused on the response to injury, help-seeking & social support, and depression. Resulted in positive increases of help-seeking intentions, help-seeking attitudes, and depression literacy. Intervention methods show promise for using online videos to improve mental health outcomes.